Is Pollution a Giffen Good? General-Equilibrium Analysis and Some Policy Implications - VASILEV, Aleksandar (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019DO - 10.14505//jemt.v10.3(35).02, 2019)
This paper takes a simple model with pollution and environmental quality and derives some novel results. In particular, pollution is shown to be a Giffen good. This is a very important finding with clear policy implications, namely that carbon taxes (and pollution permits) are counter-productive, as they lead to increase in pollution, and instead governments should administratively set emission caps.